A review on unidirectional converters for on-board chargers in electric vehicle - Vijayakumar, S.; Sudhakar, N. (Frontiers in Energy Research, 2022)
Transport is a vital sector for achieving sustainable development. The evolution of the electric vehicle is subject to the charging time, accessibility, and facility. On-board chargers are broadly used in the battery-electric and plug-in-electric fleets due to their easy installation and low cost. Also, it must be powerful and extremely efficient because of the constrained interior area and quick charging times. The minimization of hardware requirements and ease of interconnection problems are benefits of unidirectional charging. This review article presents an overview of charging levels, standards of chargers, and various topologies. On-board chargers pose a higher-power rating that reduces the anxiety of charging time and improves the charging facility on level-1 and level-2 grid supply. Unidirectional chargers reduce the charger size while other two-stage chargers pose a higher charging rate with various topologies. Finally, emerging charging trends in off-board charging, inductive charging, technology about vehicle-to-grid, wide-bandgap devices, and application of renewable energy uses are addressed.